CuZr-based bulk metallic glass and glass matrix composites fabricated by selective laser melting. (10th August 2021) - Deng, Liang; Zhang, Long; Kosiba, Konrad; Limbach, René; Wondraczek, Lothar; Wang, Gang; Gu, Dongdong; Kühn, Uta; Pauly, Simon
Abstract: Monolithic bulk metallic glass and glass matrix composites with a relative density above 98 % were produced by processing Cu46 Zr46 Al8 (at.%) via selective laser melting (SLM). Their microstructures and mechanical properties were systematically examined. B2 CuZr nanocrystals (30–100 nm in diameter) are uniformly dispersed in the glassy matrix when SLM is conducted at an intermediate energy input. These B2 CuZr nanocrystals nucleate the oxygen-stabilized big cube phase during a remelting step. The presence of these nanocrystals increases the structural heterogeneity as indirectly revealed by mircrohardness and nanoindentation measurements. The corresponding maps in combination with calorimetric data indicate that the glassy phase is altered by the processing conditions. Despite the formation of crystals and a high overall free volume content, all additively manufactured samples fail at lower stress than the as-cast glass and without any plastic strain. The inherent brittleness is attributed to the presence of relatively large pores and the increased oxygen content after selective laser melting.